A Late Prehistoric bison processing camp in the central Plains: Montana Creek East (14JW46) - Ritterbush, Lauren W.; Logan, Brad (My University, 2009)
Bison utilization during the Late Prehistoric period in the central Plains varied from the diffuse pattern that characterizes the Central Plains tradition to the focal pattern of the westernmost Oneota. Both patterns are represented at sites in the Lovewell locality on White Rock Creek, a tributary of the lower Republican River in north-central Kansas. Intensive bison exploitation is also represented at the Montana Creek East (14JW46) site within this locality. Abundant faunal remains indicative of marrow and bone grease processing are associated with the varied, if modest, lithic and ceramic assemblages. These do not suggest use by Oneota or Central Plains tradition peoples although a date fits the Late Prehistoric period. A buried Plains Woodland component, previously undocumented at Lovewell, indicates earlier evidence of bison hunting. Together the remains at this and certain other sites at Lovewell indicate extensive use of bison by different groups.
Keywords: Late Prehistoric; Central Plains; Marrow extraction; Bone grease; Lovewell